2011
DOI: 10.1111/j.1464-410x.2011.10360.x
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of tumour enucleation for renal cell carcinoma (RCC): results of a single‐centre prospective study

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? Nephron sparing surgery is the standard treatment for RCC up to a diameter of 7 cm, but it’s intra and postoperative morbidity is not negligable. Tumour enucleation is a nephron sparing technique with a demonstrated oncological efficacy while no prospective study evaluated its surgical results and postoperative morbidity to date. Our study adds a prospective evaluation of tumour enucleation morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…In a prospective series of 200 consecutive patients who had open SE, we reported a low rate of Clavien grade III surgical complications such as urinary fistula requiring JJ stent positioning, that was 0.5 %, and postoperative bleeding requiring superselective embolization of renal artery, that occurred in 2 % of cases [18]. These data compare favorably with the rates reported after standard PN in the best available evidence, that is 4.4 % for urinary fistula and 3.1 % for severe postoperative bleeding [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective series of 200 consecutive patients who had open SE, we reported a low rate of Clavien grade III surgical complications such as urinary fistula requiring JJ stent positioning, that was 0.5 %, and postoperative bleeding requiring superselective embolization of renal artery, that occurred in 2 % of cases [18]. These data compare favorably with the rates reported after standard PN in the best available evidence, that is 4.4 % for urinary fistula and 3.1 % for severe postoperative bleeding [23].…”
Section: Discussionmentioning
confidence: 99%
“…It represents the robotic translation of the SE technique, developed in our center over 25 years ago and become the standard of care for NSS either open and laparoscopically [5,6,[16][17][18].…”
mentioning
confidence: 99%
“…In these latter cases, when the depth of the lesion or the proximity to important vascular structures makes the procedure more challenging, the adoption of the TE technique can be decisive, as the blunt dissection provides a clear dissection plane identification, helping the surgeon to discriminate the natural cleavage plane existing between the tumor and the renal parenchyma. Moreover, TE provides maximal parenchymal preservation and minimizes incidental calyceal tearing or vascular injuries [32][33][34].…”
mentioning
confidence: 99%
“…It is has been reported a possible advantage using SE especially when facing tumors with most unfavourable nephrometry (PADUA ≥ 10; RENAL ≥ 10, totally endorenal tumors, cT1b with endophytic growth into the medulla and close to main intrarenal vessels and collecting system). However, the majority of the studies on the perioperative results of TE does not analyse subgroups of challenging tumors [6][7][8]. In a recent study, that assessed the perioperative results of SE in 244 patients, a substantial 21% had a PADUA score ≥10 thus confirming that SE might wide the technical indications of NSS including the most challenging cases [9].…”
Section: Enucleative Partial Nephrectomy: Long-term Resultsmentioning
confidence: 93%
“…Indeed, SE showed in single center prospective series a low incidence of postoperative complications requiring reintervention, a low rate of urinary fistulas and of ureteral stenting [7,9]. However, in a large multicenter prospectively derived dataset (RECORd project), a matched-pair comparison of 396 patients showed that SE and standard PN are associated with similar WIT and similar incidence of overall, surgical and medical complications [8].…”
Section: Enucleative Partial Nephrectomy: Long-term Resultsmentioning
confidence: 99%